FRACTAL ANALYSIS FOR TWO DIMENSIONAL GRANULAR SYSTEM USING CIRCLE COUNTING METHOD - MEGA PUSPITASARI (NIM: 10114034), GABRIELLA
Granular is a system of many objects, which is a dissipative system. Granular has many benefits that can be applied to everyday life. Fractal analysis was performed using the results of fractal dimensional calculations on Granular system modeling. Fractal dimension calculation process will be done by Box Counting method, but there is modification to method, that is change box calculation unit into circle, so this method known as Circle Counting method. The model chosen is Square Circle and Hexagonal Circle. Based on the simulation results, it is known that with the increase of n value in fixed r, the fractal dimension value will increase. Other model will also be reviewed, this is a model of the development of Circle Square and Hexagonal Circle. The model are model Permata 1 and model Permata 2. Based on simulation results obtained, model Permata 1 and model Permata 2 give the result that if value of n increase, the value of fractal dimension will increase also.